Simbol dan Ritual dalam Tradisi Tabut di Bengkulu: Kajian Antropologis dengan Pendekatan Teori Ruang Henri Lefebvre dan Teori Simbolik Clifford Geertz (Departement of Comparative Study of Religions, 2024)
The Tabut Tradition is one of the religious rituals passed down through generations in Bengkulu. This tradition is performed to welcome the new year, lasting for 10 days, starting from the 1st of Muharram to the 10th of Muharram. The Tabut tradition is closely related to symbols and rituals that are interwoven. In this analysis, the Tabut tradition will be explored using the spatial theory perspective of Henri Lefebvre and the symbolic anthropology of Clifford Geertz. This research is qualitative, employing a descriptive method. The approach used is anthropological, also utilizing Lefebvre's spatial theory and Geertz's symbolic theory as analytical tools. The results of this research include, among others, how social space is formed and enlivened by Tabut rituals through Lefebvre's approach. Meanwhile, Geertz's symbolic theory will help explain the meanings of the symbols used in this tradition as cultural and religious expressions. This study is descriptive, qualitative, and analytical in nature, aimed at investigating the symbolic meanings and rituals found in the Tabut tradition in Bengkulu.